Một thành tựu mới trong giáo dục - Nguyễn, Kế Hào (Bộ Giáo dục và Đào tạo, 2013)
According to the idea of educational techonology, the article covers a path and new working in reaseaching education - science by organizing experimental education. Having been undertaken by 1978-1979, this reaseaching work had carried out to experiment in large field from 1985 to 1986 and would be official strategy from 1994-1995.In this process,the educational techonology of primary schooling (first of all is teaching te chonology) is more formed, and complete. The educational techonology has got background with lined-chainof oprations, by implementing this openltionalsystem, the pupils of primary schools fully understand system of scientific concepts being basic for stucturing system of skills and studying method. Educational techonology - one of the strategies of primary schooling is transfering to schools with condition to develop system of key - schools of high quality.